1983
DOI: 10.1093/infdis/148.5.810
|View full text |Cite
|
Sign up to set email alerts
|

Selective Intrapartum Chemoprophylaxis of Neonatal Group B Streptococcal Early-Onset Disease. III. Interruption of Mother-to-Infant Transmission

Abstract: The effect of intrapartum ampicillin treatment on vertical transmission of group B streptococci (GBS) was examined in 575 prenatally colonized parturient women and their 580 newborn infants. Eighty women (43 receiving ampicillin) with premature labor and/or prolonged rupture of amniotic membranes were randomized. The other 495 were stratified into groups of 358 (31 receiving ampicillin) with no perinatal risk factors; 119 (28 receiving ampicillin) with premature labor and/or prolonged membrane rupture; and 23 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
0
5

Year Published

1991
1991
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(72 citation statements)
references
References 22 publications
1
66
0
5
Order By: Relevance
“…Many investigations have addressed this and clearly established an increased risk of EOS after 18 h of ROM. [14][15][16] Acquisition of EOS is also associated with a number of other well-described factors that, if present, would support the need to consider observation or evaluation of the newborn for infection. These include a maternal fever >38 1C, chorioamnionitis, prolonged or preterm ROM, poor prenatal care, poor maternal nutrition, a history of recurrent abortion, low birth weight, maternal substance abuse, difficulty in delivery, birth asphyxia and meconium staining.…”
Section: Early Versus Late Infectionsmentioning
confidence: 99%
“…Many investigations have addressed this and clearly established an increased risk of EOS after 18 h of ROM. [14][15][16] Acquisition of EOS is also associated with a number of other well-described factors that, if present, would support the need to consider observation or evaluation of the newborn for infection. These include a maternal fever >38 1C, chorioamnionitis, prolonged or preterm ROM, poor prenatal care, poor maternal nutrition, a history of recurrent abortion, low birth weight, maternal substance abuse, difficulty in delivery, birth asphyxia and meconium staining.…”
Section: Early Versus Late Infectionsmentioning
confidence: 99%
“…Several years after the demonstration of the efficacy of intrapartum antibiotic prophylaxis, the American Academy of Pediatrics and the American College of Obstetricians and Gynecologists both embraced the concept but issued different clinical guidelines in 1992. [1][2][3][4][5] The resultant controversy and implementation difficulties led the Centers for Disease Control and Prevention (CDC) to orchestrate the development of consensus guidelines in 1996 that were embraced by multiple organizations devoted to improving perinatal care. [6][7][8][9][10][11][12][13][14] These guidelines advocated the use of either screening for maternal group B streptococcal rectovaginal colonization or clinical risk factors to determine the need for intrapartum prophylaxis.…”
Section: Introductionmentioning
confidence: 99%
“…Several culture-based studies have reported higher carriage rates of GBS in the rectum than in the vagina [18,26,27], supporting the idea that the gastrointestinal tract is the reservoir for vaginal GBS. Meyn et al [28] showed that rectal colonization with GBS was the most significant predictor of vaginal colonization, suggesting that the vagina becomes colonized with GBS as a result of transfer of the organism from the rectum to the vagina.…”
Section: Introductionmentioning
confidence: 89%